2001
DOI: 10.1017/s0967199401001174
|View full text |Cite
|
Sign up to set email alerts
|

Significance of peristaltic squeezing of sperm bundles in the silkworm, Bombyx mori: elimination of irregular eupyrene sperm nuclei of the triploid

Abstract: Silkworm (Lepidoptera) males produce dimorphic sperm: nucleate eupyrene sperm and anucleate apyrene sperm. The eupyrene sperm are ordinary sperm to fertilise the eggs, while the function of apyrene sperm remains uncertain. After meiosis, 256 sperm cells are enclosed by a layer of cyst cells, forming a sperm bundle. We have previously documented that the nucleus of eupyrene sperm anchors to the head cyst cell, which locates at the anterior apex of the bundle, by an acrosome tubule-basal body assembly. Neither t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The slenderizing process coincides with that of Bombyx mori spermatogenesis (Kawamura et al, 2000). Elimination of irregular eupyrene nuclei in the silkworm is an important function of peristaltic squeezing (Kawamura et al, 2001). Insects other than Bombyx probably use the same mechanism to avoid irregular fertilization.…”
Section: Discussionmentioning
confidence: 68%
“…The slenderizing process coincides with that of Bombyx mori spermatogenesis (Kawamura et al, 2000). Elimination of irregular eupyrene nuclei in the silkworm is an important function of peristaltic squeezing (Kawamura et al, 2001). Insects other than Bombyx probably use the same mechanism to avoid irregular fertilization.…”
Section: Discussionmentioning
confidence: 68%
“…Apyrene sperm bundles in DH males and eupyrene sperm bundles in triploid males had been confirmed to be morphologically abnormal (Kawamura et al, 2001, Sahara and. Eupyrene sperm bundles in DH males and apyrene sperm bundles in triploid males, however, accomplish maturity through peristaltic squeezing (Kawamura et al, 2000(Kawamura et al, , 2001Sahara and Kawamura, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Eupyrene sperm bundles in DH males and apyrene sperm bundles in triploid males, however, accomplish maturity through peristaltic squeezing (Kawamura et al, 2000(Kawamura et al, , 2001Sahara and Kawamura, 2002). It was previously ascertained that these males produce few offspring (0 to 0.10%), but fertility is greatly improved by copulation of both types of males with a single female (74.64 to 78.74%) .…”
Section: Resultsmentioning
confidence: 99%
“…Some morphological differences between eupyrene and apyrene sperm in the process of spermatogenesis are documented in (Osanai et al, 1989) and dissociation of eupyrene sperm bundles by acids and endopeptidase (Osanai & Isono, 1997). Kawamura et al (2001) showed that the peristaltic squeezing that occurs at the very late stage of spermatogenesis eliminates the nuclei of polyploid eupyrene sperm bundles. Sugai & Kiguchi (1967) reported that the treatment of male silkworm pupae with a high temperature produces highly sterile individuals.…”
Section: Introductionmentioning
confidence: 99%